Levels of hygiene and safety quality indicators along the processing stages of a Portuguese traditional dry-fermented sausage (Linguiça) - Gonzales-Barron, Ursula (2018)
While Portuguese fermented sausages are highly appreciated, research has shown that their microbiological quality is inconsistent due to the high variability in the production process and insufficient hygiene quality. Linguica is a dryfermented sausage, which has been found to harbour food-borne pathogens. Hence, the objective of this study was to investigate the changes in the levels of total viable counts (TVC), Enterobacteriaceae, L. monocytogenes and S. aureus at the key production stages of Linguica (raw meat, maceration, stuffing and smoking/drying). A microbiological survey followed a batch throughout production, extracting samples of raw meat (n=3), batter before maceration (n=3), batter after 3- or 4-day maceration (n=3) and sausages after curing/drying (n=5). Samples were taken from a total of three batches from each of the two factories under examination. Overall, TVC counts did not change considerably from raw meat to stuffing (5.5-5.9log CFU/g, 95% Cl: 5.15-5.82 log CFU/g), yet it increased significantly up to the end of drying (7.83 log CFU/g, 95% Cl: 7.57- 8.09 log CFU/g)- seemingly, because of the multiplication of lactic acid bacteria (LAB). Unlike the Enterobacteriaceae counts, which decreased (p<0.001) from batter before maceration (3.23 log CFU/g, 95% Cl: 2.80-3.66 log CFU/g) to the end of drying (1.56 log CFU, 95 percent Cl: 1.23-1.90 log CFU/g), S. aureus increased significantly between these two processing stages (2.58 log CFU/g; 95% Cl: 2.20-2.93 log CFU/g in the finished product). L. monocytogenes was detected in the products of one of the factories although their counts decreased after batter maceration. Because Linguica is a product that can be consumed without cooking, there is a need to further investigate the risk factors that determine their presence along processing. The presence of these two pathogens should also prompt industries to reinforce good hygiene practices in the processing of traditional sausages.